Peranan Implementasi Tata Kelola Teknologi Informasi (IT Governance) sebagai Faktor Penting dalam Meningkatkan Kinerja Perusahaan - Defriko Gusma Putra; Rita Rahayu (Universitas Negeri Padang, 2020)
The application of information technology governance (IT Governance) plays an important role in utilizing information technology to fit the company's vision, mission and goals. However, there are still many companies that have not implemented IT Governace due to various factors such as: the existence of internal companies that refuse the application of information technology, the limited human resources who master information technology competence, the unavailability of frameworks and policy foundations in the information technology environment, the lack of commitment from top management, the high cost of investment in IT Governance and so on. The greater use of technology has not been accompanied by greater support for the achievement of strategies so that investments made are in vain. research and research results show that the lack of understanding of IT Governance makes unproductive investments made by companies. The method used in this research is descriptive qualitative which presents a systematic review of the problems in the implementation of Information Technology Governance (IT Governance).